2015
DOI: 10.1099/jgv.0.000252
|View full text |Cite
|
Sign up to set email alerts
|

In vitro properties of hordeivirus TGB1 protein forming ribonucleoprotein complexes

Abstract: Hordeivirus movement protein encoded by the first gene of the triple gene block (TGB1 protein, TGBp1) interacts in vivo with viral genomic and subgenomic RNAs to form ribonucleoprotein (RNP) particles that are considered to be a form of viral genome (non-virion transport form) capable of cell-to-cell and long-distance transport in infected plants. The structures of these RNPs have not been elucidated. The poa semilatent virus (PSLV) TGBp1 contains a structured C-terminal NTPase/helicase domain and an N-termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…However, hordei-like TGB1 proteins alone are incapable of independent intracellular trafficking to PD [ 10 ], but the extent to which they contribute to PD SEL modifications when expressed with other viral proteins has not been previously determined. Hordeivirus TGB1 proteins have three domains, a disordered extreme N-terminal domain (NTD), an internal domain (ID), and a C-terminal ATPase/helicase domain (HELD) [ 63 ]. Previous studies have shown that the NTD and ID domains are responsible for homologous protein-protein interactions and that TGB1 has multiple RNA binding sites [ 22 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, hordei-like TGB1 proteins alone are incapable of independent intracellular trafficking to PD [ 10 ], but the extent to which they contribute to PD SEL modifications when expressed with other viral proteins has not been previously determined. Hordeivirus TGB1 proteins have three domains, a disordered extreme N-terminal domain (NTD), an internal domain (ID), and a C-terminal ATPase/helicase domain (HELD) [ 63 ]. Previous studies have shown that the NTD and ID domains are responsible for homologous protein-protein interactions and that TGB1 has multiple RNA binding sites [ 22 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In plants, ZAR1, a plant resistance protein, also requires ATP to induce structural remodeling and assembly into a functionally pentameric ZAR1 resistosome [ 67 ]. Hordei-like TGB1 proteins also multimerize into high-molecular-weight complexes that disassemble into monomers upon incubation with ATP [ 63 ]. Based on these results, we propose that TGB1 conformational changes and assembly of vRNP movement complexes require ATP hydrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to viruses with potex-like TGB, the viral movement mediated by the hordei-like TGB does not require no the viral CP [54] . As an alternative to the virion as a genome transport form of viruses with potex-like TGB, the RNAs of viruses with hordei-like TGB form RNP complexes with TGB1 [159] [161] . In hordei-like TGBs, the TGB3 interacts with TGB2 and the TGB1/RNA complexes to form a movement-competent form of virus genome that is directed to PD in connection with the ER [18] , [127] , [137] , [138] , [158] .…”
Section: Triple Gene Blockmentioning
confidence: 99%
“…An essential step for realization of hordeivirus TGBp1 structural functions such as formation or remodeling/destabilization of transport RNP particles is based on the protein secondary structure conversion [1] .…”
Section: Datamentioning
confidence: 99%
“… This data article is related to the research article entitled “ in vitro properties of hordeivirus TGB1 protein forming ribonucleoprotein complexes” (Makarov et al, 2015 [1] ), demonstrating that upon incubation with viral RNA the poa semilatent hordeivirus (PSLV) TGB1 protein (the movement 63 K protein encoded by the first gene of the triple gene block) in vitro forms RNP structures resembling filamentous virus-like particles and its internal domain (ID) performs a major structural role in this process. This article reports the additional results on the structural lability of ID and the structural transitions in the C-terminal NTPase/helicase domain (HELD) induced by interaction with tRNA and phosphorylation.…”
mentioning
confidence: 99%